2022
DOI: 10.1186/s13054-022-04034-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant ACE2 protein protects against acute lung injury induced by SARS-CoV-2 spike RBD protein

Abstract: Background SARS-CoV-2 infection leads to acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Both clinical data and animal experiments suggest that the renin–angiotensin system (RAS) is involved in the pathogenesis of SARS-CoV-2-induced ALI. Angiotensin-converting enzyme 2 (ACE2) is the functional receptor for SARS-CoV-2 and a crucial negative regulator of RAS. Recombinant ACE2 protein (rACE2) has been demonstrated to play protective role against SARS-CoV and avian influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…This product could potently suppress the invasion of the mutants of SARS-CoV-2 generated through sequential passage in mammalian cells [ 277 ]. A recent animal study revealed how the impact of RAS dysregulation due to loss of mACE2 which leads to oxidative stress might eventuate into lung injury through activation of Ang II/AT1R/NF-κB/NOX1&2 signaling pathway [ 278 ]; the deadly signaling cascade that had hypothetically been proposed as the pathophysiologic basis of lung inflammation in early weeks of SARS-CoV-2 pandemic [ 279 ]. According to this study, rhsACE2 was found to be able to cleave Ang I and Ang II to angiotensin (1–9) and angiotensin (1–7), respectively.…”
Section: Clinical Evidence Showing Benefit Of Recombinant Human Solub...mentioning
confidence: 99%
“…This product could potently suppress the invasion of the mutants of SARS-CoV-2 generated through sequential passage in mammalian cells [ 277 ]. A recent animal study revealed how the impact of RAS dysregulation due to loss of mACE2 which leads to oxidative stress might eventuate into lung injury through activation of Ang II/AT1R/NF-κB/NOX1&2 signaling pathway [ 278 ]; the deadly signaling cascade that had hypothetically been proposed as the pathophysiologic basis of lung inflammation in early weeks of SARS-CoV-2 pandemic [ 279 ]. According to this study, rhsACE2 was found to be able to cleave Ang I and Ang II to angiotensin (1–9) and angiotensin (1–7), respectively.…”
Section: Clinical Evidence Showing Benefit Of Recombinant Human Solub...mentioning
confidence: 99%
“…In patients, ARBs is preferred over ACEi for first line hypertension treatment and discontinuing treatment is not required ( Abbasi, 2021 ; Lopez et al, 2021 ). Since, the activation of AT1R by Ang II induces ROS through the NADPH oxidase pathway and activates the hypoxia-inducible factor (HIF)-1α leading to the synthesis of the transient receptor potential channel ankyrin repeat (TRPA1) which controls intracellular calcium increase and potentially contributes to pulmonary inflammation, it was also suggested to use calcium channel blokers as an alternative to ACEi and ARBS ( Fang and Karakiulakis, 2020 ; Tignarelli et al, 2020 ; Devaux and Raoult, 2022 ; Zhang et al, 2022 ). Moreover, acting on HIF-1α, may improve the outcome of COVID-19 by decreasing hypoxia ( Devaux and Raoult, 2022 ).…”
Section: Targeting Ace2 For the Therapeutic Prevention Of Severe Form...mentioning
confidence: 99%
“…This has also opened the way to modified ACE2 for gene transfer ( Guignabert et al, 2018 ). It was recently demonstrated that recombinant ACE2 is effective for treating SARS-CoV-2 RBD protein-aggravated LPS-induced acute lung injury in a mouse experimental model and that the protection occurs by acting on the ACE2-AngII-AT1R-NOX1/2 axis that is otherwise overactivated by the SARS-CoV-2 infection ( Zhang et al, 2022 ).…”
Section: Targeting Ace2 For the Therapeutic Prevention Of Severe Form...mentioning
confidence: 99%
“…This product could potently suppress the invasion of the mutants of SARS-CoV2 generated through sequential passage in mammalian cells [269]. A recent animal study revealed how the impact of RAS dysregulation due to loss of mACE2 which lead to oxidative stress might eventuate into lung injury through activation of Ang II/AT1R/NF-κB/NOX1/2 signaling pathway [270]; the deadly signaling cascade hypothetically proposed as the pathophysiologic basis of lung inflammation in early weeks of SARS-CoV2 pandemic [271]. According to this study, rhsACE2 was found to be able to cleave Ang I and Ang II to angiotensin (1-9) and angiotensin (1-7), respectively.…”
Section: Clinical Evidence Showing Benefit Of Recombinant Human Solub...mentioning
confidence: 99%
“…According to this study, rhsACE2 was found to be able to cleave Ang I and Ang II to angiotensin (1-9) and angiotensin (1-7), respectively. Besides, this product could diminish proinflammatory factors such as TNF-α, IL-1β, IL-6 and myeloperoxidase activity in broncho-alveolar lavage fluid and ameliorate SARS-CoV2-RBD-aggravated acute lung injury provoked by administration of [270]. Additionally, considering the mouth as the most accessible gate of entry of SARS-CoV2 contaminated droplets, an ACE2-containing chewing gum has successfully been tried to reduce the high viral load in the tongue, buccal and gingival epithelial cells through entrapping the virions in the saliva and hindering the attachment of RBD with mACE2 on the mouth epithelial cells [272].…”
Section: Clinical Evidence Showing Benefit Of Recombinant Human Solub...mentioning
confidence: 99%